Analysis of Leadership Style, Communication, and Compensation on Work Morale of Government Employees - Ni Ketut Raka Utariani; Ni Nyoman Raka Astrini (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2024)
Core Values Ber-AKHLAK is an effective breakthrough of basic values for state civil apparatus in fulfilling their duties. This is because employees must have basic principles that serve as guidelines in devoting themselves in totality to the state. This study aims to analyse three variables including leadership style, communication, and compensation on the work enthusiasm of government employees. Data samples were taken by census, using an interval scale questionnaire with a value range of 1-10 and documentation. In analysing the data from the tabulation of questionnaire filling, the analysis technique used is multiple linear regression analysis technique. In analysing the strength of the relationship, the coefficient of determination analysis is used, while testing the relationship simultaneously using the F test, and in testing the relationship partially using the t-test. From data processing, the results of multiple linear regression analysis are obtained as follows, the constant is negative at -14.117. The coefficient of the leadership style variable obtained a positive value of 0.637. The coefficient of the communication variable obtained a positive value of 0.507. The coefficient of the compensation variable obtained a positive value of 0.192. So, it is concluded that overall, the independent variables of leadership style, communication and compensation have a positive and significant effect on the morale of government employees of BKB-PP Buleleng Regency. The implication of this research is to show the significance of efforts to improve the performance of government employees through work compensation received by each employee.